Hydroxyethylcellulose-Based Hydrogels Containing Liposomes Functionalized with Cell-Penetrating Peptides for Nasal Delivery of Insulin in the Treatment of Diabetes - Von Zuben, Eliete de Souza [UNESP] (2022)
Liposomes functionalized with cell-penetrating peptides are a promising strategy to deliver insulin through the nasal route. A hydrogel based on hydroxyethylcellulose (HEC) aqueous solution was prepared, followed by a subsequent addition of liposomes containing insulin solution functionalized with trans-activator of transcription protein of HIV-1 (TAT) or Penetratin (PNT). The formulations were characterized for rheological behavior, mucoadhesion, syringeability, in vitro release and in vivo efficacy. Rheological tests revealed non-Newtonian fluids with pseudoplastic behavior, and the incorporation of liposomes (HLI, HLITAT and HLIPNT) in hydrogels did not alter the behavior original pseudoplastic characteristic of the HEC hydrogel. Pseudoplastic flow behavior is a desirable property for formulations intended for the administration of drugs via the nasal route. The results of syringeability and mucoadhesive strength from HEC hydrogels suggest a viable vehicle for nasal delivery. Comparing the insulin release profile, it is observed that HI was the system that released the greatest amount while the liposomal gel promoted greater drug retention, since the liposomal system provides an extra barrier for the release through the hydrogel. Additionally, it is observed that both peptides tested had an impact on the insulin release profile, promoting a slower release, due to complexation with insulin. The in vitro release kinetics of insulin from all formulations followed Weibull’s mathematical model, reaching approximately 90% of release in the formulation prepared with HEC-based hydrogels. Serum insulin levels and the antihyperglycemic effects suggested that formulations HI and HLI have potential as carriers for insulin delivery by the nasal pathway, a profile not observed when insulin was administered by subcutaneous injection or by the nasal route in saline. Furthermore, formulations functionalized with TAT and PNT can be considered promoters of late and early absorption, respectively.